Efektifitas Terapi Akkupuntur Terhadap Keberhasilan Rehabiltasi Pasien Pasca Stroke: Literature Review - Pratama, Koernia Nanda; Alivian, Galih Noor (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction. Stroke is a sortie that occurs in the brain that involves blood vessels in the brain (blockage or cracked) and finally manifests in a various of symptoms (starting from paralysis, interference of swallowing and speaking, etc.). This disease is differentiated into ischemic-infarct strokes and hemorrhagic strokes. In Indonesia, this disease has increased from 7% to 10.9%. It indicates that stroke is a disease that is quite dangerous and needs an appropriate handling or rehabilitation.Objective. This study aims to collect and analyze articles relating to the effectiveness of acupuncture therapy as a stroke management.Method. Search for journal articles is done electronically by using several databases, namely DOAJ, PubMed and Google Scholar with the keywords